ANDROGEN-SECRETING OVARIAN STEROID CELL TUMOR: A RARE CASE OF POSTMENOPAUSAL HIRSUTISM AND POLYCYTHEMIA - Lim, Jing Li; Tee, Hwee Ching; Ho, Jin Hui; Tham, Joon Hi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Ovarian steroid cell tumours are very rare sex hormone secreting sex-cord stromal tumours with malignant potential. Steroid cell tumours account for <0.1% of all ovarian tumours. They can occur in females at any age, ranging from 2-80 years old, with the mean age of presentation at around 40 years, most of which are associated with androgenic changes (56 77%), oestrogen secretion in 6-23% and Cushing syndrome in 6-10%. Erythrocytosis can also occur as a result of high testosterone levels. CASE We report a rare case of ovarian steroid cell tumour presenting with postmenopausal hirsutism and polycythaemia. A 54-year-old postmenopausal female presented with 2 years history of hirsutism, hoarseness of voice and polycythaemia. A markedly elevated testosterone level at 15.88nmol/l and polycythaemia were noted at initial evaluation. Computed tomography of the abdomen and pelvis revealed a left adnexal solid mass (5.3 x 6.7 x 5.9 cm), for which she underwent extra fascial hysterectomy with bilateral salpingo-oophorectomy, infragastric omentectomy, left pelvic lymph node dissection and appendicectomy. Histopathology revealed not otherwise specified subtype of ovarian steroid cell tumours. Within two months of surgery, she showed regression of hirsutism. Polycythaemia and testosterone levels were also normalized after operation. CONCLUSION This case highlights the importance of considering a neoplastic source of hyperandrogenism in postmenopausal hirsutism with markedly elevated testosterone levels. Bilateral rather than unilateral salpingo-oophorectomy is the treatment of choice for steroid cell ovarian tumour in postmenopausal patients because of the high likelihood of pathological changes in the contralateral ovary.